2017
DOI: 10.1007/s10792-017-0719-8
|View full text |Cite
|
Sign up to set email alerts
|

Timing of vitrectomy for retained lens fragments after cataract surgery

Abstract: Clinical outcomes were similar in patients undergoing early and late vitrectomy. Patients with poorer baseline visual acuity were more likely to receive early vitrectomy. Worse final visual acuity was seen in patients with baseline diagnosis of diabetes and in those who experienced post-operative complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…One study comparing early (less than 7 days after cataract surgery) versus late (7 or more days after cataract surgery) vitrectomy for retained posterior segment lens fragments found similar clinical outcomes between the two groups. 16 Our patient deferred vitrectomy for removal of the lens fragment, and his intraocular inflammation resolved after aspiration of the material from the anterior chamber. In the context of retained lens fragments, corneal edema may result from a prolonged inflammatory reaction or mechanical damage to the endothelium and may require endothelial keratoplasty.…”
Section: Discussionmentioning
confidence: 73%
“…One study comparing early (less than 7 days after cataract surgery) versus late (7 or more days after cataract surgery) vitrectomy for retained posterior segment lens fragments found similar clinical outcomes between the two groups. 16 Our patient deferred vitrectomy for removal of the lens fragment, and his intraocular inflammation resolved after aspiration of the material from the anterior chamber. In the context of retained lens fragments, corneal edema may result from a prolonged inflammatory reaction or mechanical damage to the endothelium and may require endothelial keratoplasty.…”
Section: Discussionmentioning
confidence: 73%
“…As against this, some authors have shown that the type of IOL used impacts the final visual outcomes. [ 13 , 16 , 17 ] Peck et al . [ 16 ] observed that anterior chamber IOL placement at the time of cataract extraction was linked to poorer ultimate visual acuity, when compared to sulcus placed IOLs or leaving the patient aphakic.…”
Section: Discussionmentioning
confidence: 99%
“…Others have noted a trend toward higher rates of glaucoma in the early vitrectomy group, likely due to selection bias. Higher preoperative intraocular pressure leads to both early PPV and higher postoperative pressure [27]. A recent study showed lower incidence of postoperative ocular hypertension (17% compared to rates of 46--100% in the literature) and higher incidence of postoperative hypotony in patients undergoing PPV.…”
Section: Intraocular Pressurementioning
confidence: 94%